Ancient Mesopotamian Stone Bridge: Numerical Modeling and Structural Assessment - Feirusha Salih Hamad (Shock and Vibration)
This study aimed to investigate the stress-strain and strain energy density (SED) states of Dalal stone arch bridge in Mesopotamia. Structural modeling of ancient bridge made of natural stone has been proven reliable, and accurate results have been obtained using 3D finite elements. Based on the more applicable theories of failure, a general methodology is presented for evaluating the ringstone of the largest ellipse-shaped arch of the Dalal Bridge. The elliptical arch was built in the COMSOL Multiphysics complex using 70 3D elements to represent the number of stones used along the length of the arch in the Dalal Bridge. Therefore, to create an accurate model, the coordinates of the four nodes of each stone were entered. Then, all domains were extruded for 0.8 m in the y-axis direction, i.e., 0.8 m of the bridge width was selected for investigation. That is, tapered fields were used to represent the stones of the arch ring. Using Rankine’s, St. Venant’s, and Haigh’s theories, the qualitative and quantitative characteristics of all components of the stresses and SED states are investigated. The maximum positive values of the principal stresses, σ1, σ2, and σ3, in the 3D model reach 1.4, 0.51, and 0.09 MPa, respectively, and their maximum negative values were 13, 6.8, and 3.4 MPa, respectively. The equivalent principal stresses determined via a 2D investigation did not exceed these values. Evaluating the ringstone against the maximum principal strain theory (i.e., St. Venant’s theory) reveals a safety factor of four in the existing state. Also, application of Haigh’s theory confirms the results of the previously applied approaches. Even though the safety of the arch, according to the total strain energy theory (i.e., Haigh’s approach), has been verified, a significant variation in the nonuniformity of the distribution of the SED (0.0011 J/m3–4416 J/m3) confirmed that the geometry of the investigated arch is not optimal for applied loading. The maximum value of the vertical component of the displacement is 3.4 mm, significantly lower than the allowable deflection for such an arch span.